(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Crafts related to metalworking on the territory of Karakalpakstan originated in ancient times, even when people learned to make copper and bronze objects. This is confirmed by archaeological materials. The ancient population of the Southern Aral Sea region in the second half of the II millennium BC used a number of locally produced items. This is evidenced by the unique discovery of a stone casting mold for casting a spear tip from the settlement of Dzhanbas-21 [Itina 1977: p. 131] and many metal products of various kinds, identified by archaeologists in settlements and settlements on the territory of Karakalpakstan. Ancient sources provide information about the use of various metals by the Sako-Massagetian tribes [Herodotus 1972: p. 79]. Folklore data, rituals and beliefs associated with the personality of the blacksmith, workshop and tools testify to the antiquity of the blacksmith craft among the Karakalpaks. The ancient traditions of the Karakalpaks in blacksmithing are evidenced, along with written sources, by local legends about the origin of blacksmithing, about the patron saint of blacksmiths Hazreti Daut, who passed on blacksmithing skills to the Karakalpaks and Uzbeks at the same time. Ethnonyms also testify to the antiquity of the Karakalpaks’ occupation in blacksmithing. For example, the Karakalpak Kazayakly clan has a division "cop usta" (many craftsmen), whose representatives have been engaged in blacksmithing. The toponymy of Karakalpakstan also reflects the occupation of the population by blacksmithing, for example, the name of the village "Zangishi" — the village of manufacturers of stirrups.